Internal stresses distribution on different cross arms orientation for lattice transmission tower on a slope in power generation infrastructure - Nor Khalid N.H.; Usman F.; Omar R.C.; Kamaruzaman K.H. (Alpha Publishers, 2023)
In power generation infrastructure, transmission tower is one of the components that function to support an overhead transmission line. The stability of the transmission tower is depending on the applied load as well as the physical shape of the tower. Since the power line is lying on various topography, some of the transmission towers have to be located on a slope. Due to the uneven leg length, the distribution of internal stresses among the transmission tower members is different, depending on the orientation of the cross arm. A simulation of a transmission tower located on a slope with two orientations of the cross arm was analyzedusing Static Linear Analysis by considering normal and broken wire conditions, which arethe possible conditions that the tower will encounter during servicing and supporting the transmission line. The compressive stress from the generated model was compared with another model produced by the industry in confirming the reliability of the result. The study discovered that both orientations have the same pattern of maximum stress distribution during normal conditions and broken wireconditions.The different orientation of the cross arm has affected the distribution of the internal stresses by 0.4% difference in the usage of compressive stress capacity. It was also discovered that the maximum compressive stress either in tension or compression has occurred among the main steel members depending on the location of the broken wire. 2020 Alpha Publishers. All rights reserved.